A Review of Quality of Life Measures used in Surgical Outcomes for Stage I Lung Cancers. (28th May 2018) - Yip, Rowena; Taioli, Emanuela; Schwartz, Rebecca; Li, Kunwei; Becker, Betsy J.; Tam, Kathleen; Htwe, Yu Maw; Yankelevitz, David F.; Henschke, Claudia I.
Abstract: This review summarizes the literature on QoL in early stage lung cancer patients who underwent surgery. PubMed and PsycINFO were searched. Twelve articles from 10 distinct studies were identified for a total of 992 patients. Five QoL measures were used. One study reported only on pre-surgical QoL, six only on post-surgical QoL and three studies reported on both pre- and post-surgical QoL. Timing for the administration of post-surgical QoL surveys varied. The literature on QoL in Stage I non-small-cell lung cancer patients is very sparse. Additional research is needed to explore the impact of different surgical approaches on QoL.